Metagenomic Approach to Characterizing Disease Epidemiology in a Disease-Endemic Environment in Northern Thailand - Takhampunya, Ratree; Korkusol, Achareeya; Pongpichit, Chalermpol; Yodin, Komsan; Rungrojn, Artharee; Chanarat, Nitima; Promsathaporn, Sommai; Monkanna, Taweesak; Thaloengsok, Sasikanya; Tippayachai, Bousaraporn; Kumfao, Naruemon; Richards, Allen L.; et al. (Frontiers in Microbiology, 2019)
In this study, we used a metagenomic approach to analyze bacterial communities from diverse populations (humans, animals, and vectors) to investigate the role of these microorganisms as causative agents of disease in human and animal populations. Wild rodents and ectoparasites were collected from 2014 to 2018 in Nan province, Thailand where scrub typhus is highly endemic. Samples from undifferentiated febrile illness (UFI) patients were obtained from a local hospital. A total of 200 UFI samples were obtained and 309 rodents and 420 pools of ectoparasites were collected from rodents (n=285) and domesticated animals (n=135). The bacterial 16S rRNA gene was amplified and sequenced with the Illumina. Real-time PCR and Sanger sequencing were used to confirm the next-generation sequencing (NGS) results and to characterize pathogen species. Several pathogens were detected by NGS in all populations studied and the most common pathogens identified included Bartonella spp., Rickettsia spp., Leptospira spp., and Orientia tsutsugamushi. Interestingly, Anaplasma spp. was detected in patient, rodent and tick populations, although they were not previously known to cause human disease from this region. Candidatus Neoehrlichia, Neorickettsia spp., Borrelia spp., and Ehrlichia spp. were detected in rodents and their associated ectoparasites. The same O. tsutsugamushi genotypes were shared among UFI patients, rodents, and chiggers indicating that the chiggers found on rodents were also likely responsible for transmitting to people. Serological testing in UFI samples showed high prevalence (IgM/IgG) of Rickettsia and Orientia pathogens, most notably among samples collected during September-November. Additionally, a higher number of seropositive samples belonged to patients in the working age population (20-60 years old). The results presented here demonstrate that the increased risk of human infection or exposure to chiggers and their associated pathogen (O. tsutsugamushi) resulted in part from two important factors; working age group and seasons for rice cultivation and harvesting. Evidence of pathogen exposure was shown to occur as there was seropositivity (IgG) in UFI patients for bartonellosis as well as for anaplasmosis. Using a metagenomics, this study demonstrated the circulation and transmission of several pathogens in the environment, some of which are known causative agents of illness in human.